2011
DOI: 10.1111/j.1475-097x.2011.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow–restricted walking does not result in an accumulation of metabolites

Abstract: The American College of Sports Medicine recommends lifting a weight of at least 70% of one's concentric one repetition maximum to achieve muscular hypertrophy as it is believed that anything below this intensity does not produce significant muscle growth. Recent studies have found muscle hypertrophy to occur with low-intensity 'aerobic-like' exercise with the application of blood flow restriction (BFR) to the limbs. Previous research with low load resistance training has shown that elastic knee wraps provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 13 publications
2
34
1
1
Order By: Relevance
“…In contrast, the increase observed with cycling under BFR was small and suggests that lactate accumulation is not occurring to a great degree with this type of exercise. This corroborates previous findings observed following slow walking in combination with BFR (24).…”
Section: Whole Bood Lactatesupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, the increase observed with cycling under BFR was small and suggests that lactate accumulation is not occurring to a great degree with this type of exercise. This corroborates previous findings observed following slow walking in combination with BFR (24).…”
Section: Whole Bood Lactatesupporting
confidence: 83%
“…To illustrate, acute muscle swelling has been observed with slow (56 m/min) and fast BFR walking (87 m/min) without a significant decrease in torque (31), suggesting that muscle fatigue may not be a prominent mechanism with low intensity aerobic exercise. Further, walking at slow speeds does not result in an accumulation of metabolites in the blood (75 m/min) (24), although cycling at 40% of VO2 max does increase lactate levels over baseline values (~2 mmol/L increase) (13), albeit to a lesser extent than that observed with resistance training (26). Therefore, it appears that the predominant mechanism behind the benefits observed with BFR aerobic exercise at low intensities may be the acute increase in muscle cell volume and this increase in cell volume may also be responsible for the increased ERK ½ and p38 phosphorylation and for the decreased phosphorylation of eEF2 observed in young men walking under BFR at 55% VO2 max (32).…”
mentioning
confidence: 99%
“…However, few studies have used elastic knee wraps (17,21,23,24,36), and even fewer have used them outside of a laboratory setting with an athletic population (36). Additional research in this area will provide further insight into the use of practical BFR in those who are already well trained.…”
Section: Introductionmentioning
confidence: 95%
“…Abe et al (4) observed increased muscular strength and hypertrophy by using BFR in combination with slow treadmill walking. Although Abe did not measure metabolites, Loenneke et al (23) conducted comparable research in which lactate was assessed. Analysis revealed that slow treadmill walking using BFR did not result in metabolite accumulation.…”
Section: Introductionmentioning
confidence: 98%
“…The overall characteristics of the training protocol, combining walking and BFR, have been considerably consistent among the existent research examining both chronic (Abe et al ., , ) and acute physiological (Renzi et al ., ; Loenneke et al ., b; Ogawa et al ., ) adaptations in healthy young men. Generally, this protocol has been structured for five bouts of 2–5‐min treadmill walking, at a variable speed between 50 and 87 m min −1 , with a 1‐min rest between each bout.…”
Section: Introductionmentioning
confidence: 98%